Ternary magnesium alloy with high plasticity and high corrosion resistance and preparation method thereof
By adding an appropriate amount of Mn and Y to the magnesium alloy and adopting tilt casting and heat treatment processes, the plasticity and corrosion resistance of magnesium alloys are solved, and high-performance and low-cost magnesium alloy preparation is achieved, suitable for aerospace and automobiles and other fields.
Patent Information
- Application Number
- CN202411383494.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-03
AI Technical Summary
Traditional magnesium alloys are prone to form a substrate texture during deformation, resulting in poor room temperature plasticity and forming performance, and have poor corrosion resistance, which limits its application in aerospace and automobile fields.
A ternary magnesium alloy with 3% to 6% Mn and 0.5% to 2% Y is prepared by smelting under a protective atmosphere through a tilt casting process and solid solution and aging heat treatment to prepare a magnesium alloy with high plasticity and high corrosion resistance. .
It improves the room temperature plasticity and corrosion resistance of magnesium alloys, reduces the difficulty and cost of casting, and realizes high-performance magnesium alloy preparation, which is suitable for industrial applications.
Smart Images

Figure CN119242999A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of magnesium alloy preparation, and in particular relates to a ternary magnesium alloy with high plasticity and high corrosion resistance and a preparation method thereof. Background Art
[0002] The density of magnesium is 1.74 g / cm 3 , which is much lower than the common metal aluminum (Al, 2.7g / cm 3 ), titanium (Ti, 4.5 g / cm 3 ), iron (Fe, 7.9 g / cm 3 ), is the lightest engineering metal. In addition, magnesium and its alloys have the advantages of high specific strength, good processing performance, good thermal conductivity, etc., and have broad application prospects in aerospace and automotive fields. The significant weight reduction effect also makes outstanding contributions to the realization of lightweight, energy saving and emission reduction goals. However, traditional commercial magnesium alloys are prone to form basal texture during conventional deformation, resulting in poor room temperature plasticity and forming properties, which hinders the large-scale application of magnesium alloys. In addition, the standard electrode of magnesium is -2.37V (vs.SHE), which has a high electrochemical activity, much lower than aluminum (-1.56V vs.SHE) and iron (-0.25V vs.SHE), and is extremely susceptible to corrosion by corrosive media. The MgO formed by magnesium alloys in the air reacts with Mg(OH) 2 The film layer is formed slowly and is loose and porous. The oxide or hydroxide layer generated on magnesium is soluble in most water environments or in the presence of humidity, making it difficult to provide effective protection for the substrate. Poor corrosion resistance is also a shortcoming that hinders the engineering application of magnesium alloys.
[0003] The Chinese invention patent application with the authorization number "CN107475590B" and the title "A high-strength and high-plasticity casting magnesium alloy and its preparation method" discloses a magnesium alloy, whose element mass percentage composition is: Zn 3% to 6%, Y 8% to 11%, Ca 0.4% to 0.6%, Mn 0.5% to 1.5%, impurities <0.1%, and the balance is Mg. The reference discloses that the Mn excessively distributed at the grain boundaries in the alloy can promote the diffusion of rare earth atoms into the magnesium matrix, and enrich at the crystallization front during the solidification process to prevent the growth of the ternary phase, causing the semi-continuous network of three phases to change to a discontinuous state, thereby improving the casting performance of the alloy.
[0004] The Chinese invention patent application with publication number "CN117701961A" and titled "A room temperature ultra-high plasticity, high strength, high damping, high thermal conductivity and corrosion-resistant magnesium alloy and its preparation method" discloses a room temperature ultra-high plasticity, high strength, high damping, high thermal conductivity and corrosion-resistant magnesium alloy. Alloying and grain boundary segregation are used to improve the corrosion resistance, damping performance and heat resistance of the alloy. The corrosion rate is 0.3-0.5mm / y, and a new generation of structural and functional integrated room temperature ultra-high plasticity multi-element deformation magnesium alloy has been developed.
[0005] However, the application of magnesium alloys in the fields of vehicle engineering is generally based on casting processes. Compared with deformation processes, casting processes usually have higher production efficiency and lower costs, and multi-component magnesium alloys will increase the difficulty of casting magnesium alloys, which is also one of the main reasons limiting the further expansion of magnesium alloy applications. At the same time, the corrosion rate of magnesium alloys disclosed in the above-mentioned prior art is relatively high. There is a continuous need in this field to develop magnesium alloys with high plasticity and high corrosion resistance and simple processes. Summary of the invention
[0006] The purpose of the present invention is to solve the defects and cost problems of the prior art, to improve the two major limitations of magnesium alloy application, namely poor plasticity and poor corrosion resistance, to a certain extent, and to propose a ternary magnesium alloy with high plasticity and high corrosion resistance and a preparation method thereof.
[0007] This is achieved specifically through the following technical solutions:
[0008] 1. A ternary magnesium alloy with high plasticity and high corrosion resistance, comprising the following elemental compositions by mass percentage: Mn: 3% to 6%, Y: 0.5% to 2%, and the remainder being Mg and unavoidable impurities such as Fe, Cu, Ni, etc.
[0009] Further, the ternary magnesium alloy with high plasticity and high corrosion resistance contains 3%, 4%, 5%, 6% or any range or sub-range between the aforementioned proportions of Mn.
[0010] Furthermore, the ternary magnesium alloy with high plasticity and high corrosion resistance contains 4% to 5% of Mn.
[0011] Furthermore, the ternary magnesium alloy with high plasticity and high corrosion resistance contains 4.0%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5.0% or any range or sub-range between the aforementioned proportions of Mn.
[0012] Further, the ternary magnesium alloy with high plasticity and high corrosion resistance contains Y in 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0% or any range or sub-range between the aforementioned proportions.
[0013] Furthermore, the corrosion rate of the ternary magnesium alloy with high plasticity and high corrosion resistance in a 3.5 wt. % NaCl solution at a standard room temperature of 25° C. is less than 0.30 mm / y.
[0014] 2. The method for preparing the above-mentioned ternary magnesium alloy with high plasticity and high corrosion resistance is characterized by comprising the following steps:
[0015] (1) according to the composition ratio of the ternary magnesium alloy with high plasticity and high corrosion resistance, magnesium ingot, Mg-Mn and Mg-Y master alloy raw materials are weighed and melted in a tilting melting device under a protective atmosphere to obtain a magnesium alloy melt to reach a casting state;
[0016] (2) Under a protective atmosphere, pour the magnesium alloy melt into a preheated mold and air-cool it into an ingot;
[0017] (3) The ingot is cut into blocks, and solid solution and aging heat treatments are performed to finally prepare a ternary magnesium alloy with high plasticity and high corrosion resistance.
[0018] Furthermore, the protective atmosphere is high-purity argon gas (purity ≥ 99.999%);
[0019] Furthermore, the melting temperature in step (1) is 670°C to 720°C;
[0020] Furthermore, the preheated mold temperature in step (2) is 140°C to 180°C, and the air cooling time is 20min to 60min;
[0021] Furthermore, the thickness of the blocks after cutting in step (3) is 5 mm to 10 mm, the solution treatment temperature is 420° C. to 480° C., the time is 4 h to 10 h, and then water quenching is performed.
[0022] Furthermore, the post-solution aging heat treatment temperature in step (3) is 200°C to 250°C for 6h to 12h, and after water quenching, a ternary magnesium alloy with high plasticity and high corrosion resistance is obtained.
[0023] Beneficial effects:
[0024] (1) The tilting pouring method adopted by the present invention can effectively reduce the drop of the magnesium alloy melt after entering the mold cavity, reduce the oxidation slag generated when the aluminum liquid splashes, and at the same time avoid the phenomenon of air entrapment, reduce the generation of pores, and improve the density and quality of the casting. In addition, tilting pouring can reduce the oxidation of the metal liquid and the mixing of inclusions, which is beneficial to improving the corrosion resistance and mechanical properties of the casting.
[0025] (2) In the present invention, low-content Mn and Y are added to form a ternary magnesium alloy, which has low cost and lower casting difficulty than multi-component magnesium alloys. The addition of a small amount of Mn reduces the formation of the second phase, which helps to reduce the generation of cracks. The segregation of Mn at the grain boundary can reduce the grain boundary energy and promote grain boundary sliding, thereby improving the plasticity at room temperature. The addition of Y with a large PBR value makes the film layer generated on the alloy surface more dense, effectively hinders the penetration of corrosive ions, and improves the corrosion resistance of the alloy.
[0026] (3) After solution treatment and aging heat treatment, the second phase content becomes less and a more uniform structure is formed, which improves the mechanical properties of the magnesium alloy. The reduction of the second phase reduces the galvanic corrosion between the second phase and the matrix, which is more conducive to promoting the formation of a uniform corrosion film. After immersion in 3.5ωt% NaCl solution for 7 days, the measured hydrogen evolution corrosion rate was 0.216mm / y, the yield strength was 169MPa, the tensile strength was 227MPa, and the elongation was 17.6%.
[0027] (4) The high plasticity and high corrosion resistance ternary magnesium alloy prepared by the present invention achieves the unity of high plasticity and high corrosion resistance of magnesium alloy and strength performance by a simple and easy to industrialize method. It has excellent performance and relatively low cost, and the casting difficulty is lower than that of multi-element alloys, and has good industrial application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is an electron backscatter diffraction photograph of the ternary magnesium alloy with high plasticity and high corrosion resistance prepared in Example 1;
[0029] Figure 2 This is a photo of the morphology of the ternary magnesium alloy micro-pillar compression test with high plasticity and high corrosion resistance prepared in Example 1;
[0030] Figure 3 A typical tensile curve diagram of the ternary magnesium alloy with high plasticity and high corrosion resistance prepared in Example 1;
[0031] Figure 4 This is a graph of hydrogen evolution of the ternary magnesium alloy with high plasticity and high corrosion resistance prepared in Example 1 in 3.5ωt% NaCl solution for 7 days. DETAILED DESCRIPTION
[0032] The specific embodiments of the present invention are further described in detail below, but the present invention is not limited to these embodiments, and any improvement or substitution based on the basic spirit of the present embodiment still falls within the scope of protection required by the claims of the present invention.
[0033] Example 1
[0034] In the method for preparing a high-plasticity and high-corrosion-resistant ternary magnesium alloy in this embodiment, the master alloy and the magnesium ingot are polished with 320-mesh sandpaper to remove the surface oxide layer and impurities, and the following steps are performed:
[0035] (1) according to the composition ratio of the ternary magnesium alloy with high plasticity and high corrosion resistance, magnesium ingot, Mg-Mn and Mg-Y master alloy raw materials are weighed, and the magnesium ingot, Mg-Mn and Mg-Y master alloy raw materials with a purity of not less than 99.9% are melted in a tilting melting device at 700° C. under a protective atmosphere (the protective gas is high-purity argon gas with a purity of ≥99.999%) to obtain a magnesium alloy melt to reach a casting state;
[0036] (2) Under a protective atmosphere, the magnesium alloy melt is poured into a mold preheated to 150°C and air-cooled into an ingot for 30 minutes;
[0037] (3) The ingot was cut into blocks with a thickness of 5 mm, solution treated at 460° C. for 8 h in a tube furnace, and water quenched; then aged at 200° C. for 10 h in a tube furnace, and finally a ternary magnesium alloy Example 1 with high plasticity and high corrosion resistance was prepared.
[0038] The specific components including mass percentage are shown in Table 1, and the balance is Mg and other inevitable impurities such as Fe, Cu, Ni, etc.
[0039] Table 1
[0040]
[0041] Example 2
[0042] In the method for preparing a high-plasticity and high-corrosion-resistant ternary magnesium alloy in this embodiment, the master alloy and the magnesium ingot are polished with 320-mesh sandpaper to remove the surface oxide layer and impurities, and the following steps are performed:
[0043] (1) according to the composition ratio of the ternary magnesium alloy with high plasticity and high corrosion resistance, magnesium ingot, Mg-Mn and Mg-Y master alloy raw materials are weighed, and the magnesium ingot, Mg-Mn and Mg-Y master alloy raw materials with a purity of not less than 99.9% are melted in a tilting melting device at 700° C. under a protective atmosphere (the protective gas is high-purity argon gas with a purity of ≥99.999%) to obtain a magnesium alloy melt to reach a casting state;
[0044] (2) Under a protective atmosphere, the magnesium alloy melt is poured into a mold preheated to 150°C and air-cooled into an ingot for 30 minutes;
[0045] (3) The ingot was cut into blocks with a thickness of 5 mm, solution treated at 460° C. for 8 h in a tube furnace, and water quenched; then aged at 200° C. for 10 h in a tube furnace, and finally a ternary magnesium alloy Example 2 with high plasticity and high corrosion resistance was prepared.
[0046] The specific components including mass percentage content are shown in Table 2, and the balance is Mg and other inevitable impurities such as Fe, Cu, Ni, etc.
[0047] Table 2
[0048]
[0049] Example 3
[0050] In the method for preparing a high-plasticity and high-corrosion-resistant ternary magnesium alloy in this embodiment, the master alloy and the magnesium ingot are polished with 320-mesh sandpaper to remove the surface oxide layer and impurities, and the following steps are performed:
[0051] (1) according to the composition ratio of the ternary magnesium alloy with high plasticity and high corrosion resistance, magnesium ingot, Mg-Mn and Mg-Y master alloy raw materials are weighed, and the magnesium ingot, Mg-Mn and Mg-Y master alloy raw materials with a purity of not less than 99.9% are melted in a tilting melting device at 700° C. under a protective atmosphere (the protective gas is high-purity argon gas with a purity of ≥99.999%) to obtain a magnesium alloy melt to reach a casting state;
[0052] (2) Under a protective atmosphere, the magnesium alloy melt is poured into a mold preheated to 150°C and air-cooled into an ingot for 30 minutes;
[0053] (3) The ingot was cut into blocks with a thickness of 5 mm, solutionized at 440° C. for 6 h in a tubular furnace, and water quenched; then aged at 220° C. for 8 h in a tubular furnace, and finally, Example 3 of the ternary magnesium alloy with high plasticity and high corrosion resistance was prepared.
[0054] The specific components including mass percentage are shown in Table 3, and the remainder is Mg and other inevitable impurities such as Fe, Cu, Ni, etc.
[0055] Table 3
[0056]
[0057] Comparative Example 1
[0058] In the method for preparing a high-plasticity and high-corrosion-resistant ternary magnesium alloy in this comparative example, the master alloy and the magnesium ingot are polished with 320-mesh sandpaper to remove the surface oxide layer and impurities, and the following steps are performed:
[0059] (1) according to the composition ratio of the ternary magnesium alloy with high plasticity and high corrosion resistance, magnesium ingot, Mg-Mn and Mg-Y master alloy raw materials are weighed, and the magnesium ingot, Mg-Mn and Mg-Y master alloy raw materials with a purity of not less than 99.9% are melted in a tilting melting device at 700° C. under a protective atmosphere (the protective gas is high-purity argon gas with a purity of ≥99.999%) to obtain a magnesium alloy melt to reach a casting state;
[0060] (2) Under a protective atmosphere, the magnesium alloy melt is poured into a mold preheated to 150°C and air-cooled into an ingot for 30 minutes;
[0061] (3) The ingot was cut into blocks with a thickness of 5 mm, solutionized at 460° C. for 8 h in a tube furnace, and water quenched; then aged at 220° C. for 10 h in a tube furnace, and finally a ternary magnesium alloy comparative example 1 with high plasticity and high corrosion resistance was prepared.
[0062] The specific components including mass percentage content are shown in Table 4, and the balance is Mg and other inevitable impurities such as Fe, Cu, Ni, etc.
[0063] Table 4
[0064]
[0065] Performance Test:
[0066] 1. The high plasticity and high corrosion resistance ternary magnesium alloy prepared in Example 1 was observed by electron backscatter diffraction under a scanning electron microscope. The results are as follows: Figure 1 As shown in the figure, the rapid solidification by tilt casting has a high cooling rate, so the grain size of the alloy is smaller than that of the conventional solidification method. Magnesium alloys with smaller grain sizes have higher strength and a greater dislocation density at the grain boundary, which also weakens the barrier effect of the grain boundary on dislocations, thereby promoting the activity of grain boundary sliding. At the same time, it can also reduce the corrosion sensitivity of the grain boundary and is conducive to the formation of a denser oxide film, thereby slowing down the development of corrosion.
[0067] 2. Hydrogen evolution immersion test
[0068] The high plasticity and high corrosion resistance ternary magnesium alloys obtained in Examples 1-3 and Comparative Example 1 were immersed in a 3.5ωt% NaCl solution for 168 hours and subjected to a hydrogen evolution immersion test. The results are shown in Table 5.
[0069] Table 5
[0070]
[0071]
[0072] It can be seen from Table 5 that the high plasticity and high corrosion resistance ternary magnesium alloy prepared by the present invention is immersed in a 3.5ωt% NaCl solution at room temperature for 168 hours, and the hydrogen evolution rate is no more than 0.136mL cm-2·day-1, and the corresponding hydrogen evolution corrosion rate is 0.284mm / y, which is lower than the corrosion rate of the ultrapure magnesium alloy of 0.30mm / y. In comparative example 1, the Y content is too high, and the excessive precipitation of the second phase will aggravate the galvanic corrosion effect between the matrix and the corrosion, and the corrosion is accelerated. The hydrogen evolution rate is 0.457mL cm-2·day-1 when immersed in a 3.5ωt% NaCl solution at room temperature for 168 hours, and the corresponding hydrogen evolution corrosion rate is 0.954mm / y, which is far higher than the corrosion rate of the ultrapure magnesium alloy of 0.30mm / y.
[0073] 3. Micro-column compression test
[0074] Crystalline oriented micropillars with a diameter of 5 μm were fabricated using focused ion beam (FIB) processing and then compressed at room temperature. Figure 2 The slip trace analysis of the deformed column shows that multi-system slip and cross slip occurred, which promoted the activation of the non-basal slip system and improved the plasticity of the alloy.
[0075] Unless otherwise specified, all percentages herein are by mass.
[0076] Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs.
[0077] Although the present invention has selected the preferred embodiments disclosed above, it is not intended to limit the present invention. Any researcher in the field can use the design parameters and contents in the above disclosed embodiments to change and modify the research scheme of the present invention without departing from the spirit and scope of the present invention. Therefore, any simple modification, parameter change and modification made to the above embodiments based on the research essence of the present invention without departing from the content of the present invention, all belong to the protection scope of the present invention.
Claims
1. A ternary magnesium alloy with high plasticity and high corrosion resistance, characterized in that: The element components contain the following mass percentages: Mn: 3% to 6%, Y: 0.5% to 2%, and the balance is Mg and unavoidable impurities such as Fe, Cu, and Ni.
2. A ternary magnesium alloy with high plasticity and high corrosion resistance as claimed in claim 1, characterized in that: The inevitable impurities include Fe, and the Fe content is ≤0.06% by mass.
3. A ternary magnesium alloy with high plasticity and high corrosion resistance as claimed in claim 1, characterized in that: The element composition comprises the following mass percentages: Mn: 4.12%, Y: 0.67%; the balance is Mg and other inevitable impurities such as Fe, Cu, and Ni.
4. A ternary magnesium alloy with high plasticity and high corrosion resistance as claimed in any one of claims 1 to 3, characterized in that: The corrosion rate of the ternary magnesium alloy with high plasticity and high corrosion resistance in a 3.5wt.% NaCl solution at a standard room temperature of 25°C is less than 0.30 mm / y.
5. A method for preparing a ternary magnesium alloy with high plasticity and high corrosion resistance, characterized in that: The following steps are involved: (1) according to the composition ratio of the ternary magnesium alloy with high plasticity and high corrosion resistance, magnesium ingot, Mg-Mn and Mg-Y master alloy raw materials are weighed, and the magnesium ingot, Mg-Mn and Mg-Y master alloy raw materials are melted in a tilting melting device under a protective atmosphere of high-purity argon gas to obtain a magnesium alloy melt to reach a casting state; (2) Under a protective atmosphere, pour the magnesium alloy melt into a preheated mold and air-cool it into an ingot; (3) The ingot is cut into blocks, and solid solution and aging heat treatments are performed to finally prepare a ternary magnesium alloy with high plasticity and high corrosion resistance.
6. The method for preparing a ternary magnesium alloy with high plasticity and high corrosion resistance as claimed in claim 5, characterized in that: The melting temperature in step (1) is 670°C to 720°C.
7. The method for preparing a ternary magnesium alloy with high plasticity and high corrosion resistance as claimed in claim 5, characterized in that: The preheated mold temperature in step (2) is 140°C to 180°C, and the air cooling time is 20min to 60min.
8. The method for preparing a ternary magnesium alloy with high plasticity and high corrosion resistance as claimed in claim 5, characterized in that: The thickness of the blocks after cutting in step (3) is 5 mm to 10 mm, the solution treatment temperature is 420° C. to 480° C., the time is 4 h to 10 h, and then water quenching is performed; the aging heat treatment temperature is 200° C. to 250° C., the time is 6 h to 12 h, and after water quenching, a ternary magnesium alloy with high plasticity and high corrosion resistance is obtained.
Citation Information
Patent Citations
A high-strength, high-ductility cast magnesium alloy and its preparation method
CN107475590B
Room-temperature ultrahigh-plasticity high-strength high-damping high-thermal-conductivity corrosion-resistant magnesium alloy and preparation method thereof
CN117701961A